Analysis of Problems of Oversight of the Constitutional Court - Sofi Yuliniar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Constitution through decision number 005/PUU-lV/2006 dated 23 August 2006 which raises problems in a statement that is in the articles of supervision of the judicial commission. Where the supervision of judges regarding the constitution is contrary to the 1945 Constitution of the Republic of Indonesia and does not have a binding legal power. In an oversight of constitutional judges associated with a principle of independence in which the judicial power to know the supervisory system of constitutional judges in preventing the power of judges to realize an ideal and clear oversight. The article I made aims to find out the knowledge of constitutional court oversight to prevent abuse of judicial power and constitutional court judges must also know how the existence of the constitutional court judge supervisory body in supervising constitutional court judges. This study uses the library research method or the results of research that has been carried out, as for the data used here, among others, which have references or primary legal language from legislation and decisions, secondary legal materials from books, journals, thesis, and tertiary legal material from a dictionary, encyclopedia. Where based on the analysis of the data carried out, it was obtained from a conclusion regarding the regulation of supervision of constitutional judges regarding article 21 paragraph 1 letter a where the sound is PMK constitutional court regulations number 2 of 2014 concerning the honorary assembly of the constitutional court. Where, according to the author, the internal supervision of constitutional judges has not been effective or is said to be due to several factors which have resulted in weak internal supervision, the first being the spirit of defending the conference and the absence of a genuine will from the judiciary leadership to follow up on the results of the internal supervision of judges which thus opens up opportunities for judges who are proven to have violated the code of ethics against the constitutional court. So in order for the supervision of constitutional judges to be good and ideal, the supervision must be carried out by an external supervisory institution. Yes, the judicial commission can provide more effective oversight and maintain the dignity and dignity of constitutional judges within the scope of the constitutional court.